Tea consumption affects the absorption of levothyroxine - Lai, Ying-Wen; Huang, Shih-Ming (Frontiers in Endocrinology, 2022)
Levothyroxine (LT4) is a convenient treatment for hypothyroidism. Coffee, however, prevents the body from efficaciously absorbing LT4. It is unknown whether the intake of tea interferes with LT4 absorption. Thirty-seven hypothyroidism patients with the following types of consumption were recruited: 1) only tea, 2) tea and coffee, and 3) only coffee. The concentrations of thyroid-stimulating hormone (TSH), T3, and T4 were recorded before and three months after changing the consumption. The patients had varied reductions in the concentration of TSH to varying degrees after three months (p < 0.001 or p < 0.05). The natural logarithms of the differences between the concentrations of TSH before and after the change in consumptions (Δln-TSH) of tea and coffee, only coffee, and only tea were 1.94, 2.00, and 2.18, respectively. Long-term tea, like coffee, consumption interfered with the absorption of LT4. We believe that avoiding tea when taking LT4 will reduce malabsorption.